Clinical aspects of tuberculosis pleurisy in patients with cancer of various localizations - N. A. Stogova (Туберкулез и болезни лёгких)
The objective of the study is to determine characteristics of the clinical course and treatment results of tuberculosis exudative pleurisy in patients with cancer of various localizations.Subjects and methods. Case histories of 26 patients aged 42-83 years (18 men, 8 women) with tuberculosis exudative pleurisy and concurrent cancer of various localization treated in 1985-2016 were analyzed. Those patients were compared to the group of 120 patients with tuberculosis exudative pleurisy but no concurrent cancer.Results: From 1985 to 2016, 26 (0.95%) of the 2,723 tuberculosis exudative pleurisy patients suffered from concurrent cancer of various localizations. 10/26 (38.46%) cancer patients were diagnosed 1-13 years before tuberculosis exudative pleurisy developed, all of them received combination anticancer therapy. Other risk factors of developing tuberculosis in patients with tuberculosis exudative pleurisy and cancer of various localizations were the following: exposure to a tuberculosis case (15%), residual changes after previous tuberculosis (38.5%), elderly and senile age (61.5%), and comorbidities (77%). The treatment effectiveness of tuberculosis exudative pleurisy in them was lower compared to the patients without cancer: cure with minimal pleural overlays was less frequent (p1-2 < 0.05; χ2); pleural exudation persisted for a longer period of time (p1-2 < 0.01; χ2); the serous exudate transferred into purulent one more often(p1-2 < 0.05; χ2).